PEMANFAATAN E-LEARNNG SEBAGAI SALAH SATU BENTUK PENERAPAN TIK DALAM PROSES PEMBELAJARAN - Nugroho, Ariyawan Agung (MAJALAH ILMIAH PEMBELAJARAN, 2008)
The implementation of Information and Communication Technology in learning process has been consciously or unconsciously insperabale to the learning process in classroom. The positive impacts it brings has been tremendous including creating opportunities flexibily accessed by students anywhere and anytime, enriching learning materials, enlivening learning process, making learning process more open, improving the effectiveness of teaching and learning process and promoting student's autonomy. To benefit from it, educational institution either schools or universities should have been implementing it in varied ways, either complementary or substitutive. Yet, it takes a lot of energy, cost, teacher's computer skill etc to directly employ ICT in schools and universities. Applying ICT in leveled stages according to categorization defined by Tella is therefore preferable seeing the present condition generally occurs in Indonesian schools and universities. By stepping from the first, the third, the second and the forth category, schools will be more well prepared and ready to eventually implement ICT, particularly e-learning in its most advanced practice as multimedia and internet-based learning environment, which ensures the flexibility and the distributedness of the learning process among students in larger scopes. In that regard, this article is aimed at highlighting the framework of developing ICT implementation program in schools or universities by addressing their current conditions.